AL-QURAN READING AND WRITING DEVELOPMENT STRATEGY AT THE MA'HAD AL-JÂMIAH CENTER UIN MAULANA MALIK IBRAHIM MALANG - Kholil, Ahmad; Rofik Fitrotulloh , Mohamad; Solihah , Mamluatu; Utami , Ary (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
Islamic Religious Colleges (PTKI) play a key role in the development of Islamic studies, especially related to the study of the Qur'an. UIN Maliki Malang, through the Mahad Al-Jamiah Center, focuses on improving the skills of reading and writing the Qur'an with daily coaching programs. In 2019, UIN Maliki Malang achieved the highest Qur'an reading index among 14 UINs in Indonesia and ranked second in writing skills. This study discusses the management of the Qur'an coaching strategy at the Mahad Al-Jamiah Center using a qualitative descriptive method. The analysis process uses the Miles, Huberman, and Saldana approach which includes data condensation, data presentation, and drawing conclusions. The results of the study indicate that the management of Al-Qur'an ta'lim coaching combines planning, implementation, and evaluation to increase competitive advantage and achieve graduates with good Qur'an reading and writing skills, as well as Ulul Albab character. This Al-Qur'an ta'lim program is the foundation for forming graduates with the character of Ulul Albab, namely those who excel in Al-Qur'an reading and writing skills and have spiritual integrity. This strategy combines a managerial approach with a common goal, so as to be able to maintain competitive advantage in Al-Qur'an education in the Islamic higher education environment.